Transition to a Low Carbon Economy in Poland - World Bank (Washington, DC, 2014)
Transition to a low carbon economy in Poland is a study by the World Bank for the Polish Government, supported by the UK Department for International Development and donors to the Energy Sector Management Assistance Program (ESMAP). The study poses the question of how Poland, an European Union (EU) member state, an industrialized 'annex one' country for the purposes of international climate discussions, and an Organization for Economic Co-operation and Development (OECD) member, can successfully transition to a low carbon economy as successfully as it underwent transition to a market economy in the early 1990s. Transition to a low carbon economy in Poland provides a detailed assessment of many aspects of a low carbon growth strategy for Poland, developing insights via a suite of models that should provide ongoing assistance to policymakers. These policymakers may find reassuring the main message that Poland's transition to a low carbon economy, while not free or simple is affordable. However, capturing the full package of technologically feasible and economically sensible abatement measures requires coordinated and early action by the government.